PENDIDIKAN MORAL DALAM SISTEM KEKAISARAN JEPANG MODERN - Andy Bangkit Setiawan (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
Japanese Meiji Restoration in the end of 19 century is one ofinteresting theme in Japanese Studies. How Japanese changed theirpolitical, social, economic systems after Western impact happened in 1868, and how these changed legitimated ideologically is a problem which influences our view to Japan and Japanese today. This article analyzed educational revolution in Meiji Japan under their modern imperial system and analyzed how this changed legitimated ideologically.Keywords: Confucianism Moral Education, Modern Imperial System,MotodaNagazane